Trying Modified Approaches to the Management of Pregnancy Induced Diabetes Mellitus (GDM) a Prospective Study - Zia Ullah, Sabeena Umer, Bilal Habib, Farukh Bashir, Shazia Roman, Sadia Nisar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To investigate maternal and foetal outcomes in patients with gestational diabetes mellitus diagnosed according to the criteria of the International Association of Diabetes and Pregnancy Study Groups (IADPSG), but who were evaluated using a twenty-four hour seven-value sugar profile prior to the implementation of management. This study sought to examine maternal and fetal outcomes in patients with gestational diabetes mellitus. Place of Study: Sialkot Medical College Sialkot Duration of Study: JUNE 2021 TO JUNE2022 Methods: This prospective observational study was undertaken at the Sialkot Medical College Hospital over the course of one year. The hospital served as the study's location. Prior to starting any medication between 24 and 28 weeks of pregnancy, women diagnosed with GDM based on IADPSG criteria were needed to undertake a seven-value sugar profile within twenty-four hours. This criterion applied to women diagnosed with gestational diabetes between 24 and 28 weeks of pregnancy. The remaining patients were treated with medical nutrition therapy (MNT), which may or may not have been supplemented with medication depending on what was necessary to maintain their normal blood sugar levels. Documentation and analysis of maternal and fetal outcomes were conducted to assess whether or not the groups displayed differentiating characteristics. Results: GDM was diagnosed in 198 out of a total of 1867 pregnant women, representing a 9.1% prevalence rate. In 81 patients, or 40.90% of the total, the 7-point blood glucose profile (ITT) was normal, and these individuals required no medical intervention other than watchful observation. Other patients received treatment; 89 (44.9% of patients) required only MNT control, while 19 (9.59%) received supplementary medication in the form of metformin and 9 (4.5%) required insulin. It was determined that there were no statistically significant differences between the treated and untreated groups in terms of maternal–fetal outcomes. Upon comparing treated and untreated groups, this was the result that was reached. Conclusions: After an abnormal Oral Glucose Tolerance Test, the technique of evaluating patients with a seven-value, twenty-four-hour sugar profile limited the capacity of nearly one-third of women to get medication and treatment for GDM without compromising maternal–fetal outcomes. This was the case despite the absence of a link between an aberrant OGT and a diminished capacity to receive therapy and treatment for GDM. Keywords: GDM IADPSG Maternal fetal outcomes